PATTERN OF NON-VENEREAL GENITAL DERMATOSES IN ADULT MALE- A CLINICAL STUDY IN A TERTIARY CARE CENTRE - Pramanik, Maloy; Das, Suchibrata; Chowdhury, Joyeeta; achar, arun; Chatterjee, Kingshuk (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Non-venereal genital dermatoses are genital dermatoses that are not sexually transmitted. It causes extreme anxiety in patients because venereal disease is often their primary concern. The aim was to study the clinical pattern of various non-venereal genital dermatoses in males aged 18–60 years. Methods: A cross-sectional clinical study was done among male patients between 18 and 60 years of age with non-venereal genital dermatoses attending the dermatology outpatient department of a tertiary care hospital in Eastern India. Patients clinically diagnosed with non-venereal genital dermatoses were included in the study after signing the informed consent thorough examination of the genital lesion was done with special relevance to the morphology, number, tenderness, regional lymph node involvement, etc. A complete physical and systemic examination was done. Associated skin lesions were noted. Investigations such as blood sugar, Tzanck smear, KOH mount, Gram stain, and histopathological examination were done in relevant cases. At the Venereal Diseases Research Laboratory, HIV tests were done to rule out STDs. Statistical analysis was done using the necessary software. Results: A total of 133 patients were included in the study. The commonest age group was 18–30 years. The most common [35%] disease was Candidal Balano-Posthitis. Married people were more affected. Diseases predominant in rural areas were LSA. Non-STD genital dermatoses are less more common in Muslims. Diabetes is common in both personal and family histories. Conclusion: For the differentiation of non-venereal genital dermatoses, apart from history and investigations, the clinical study such as age, residence, religion, and morphology of the lesions are very important. A clinician should have an unbiased approach towards genital conditions.